Modern methods of teaching professional russian language terminology at a technical university - Шайбакова, Дамина; Курманбаева, Т. (Pedagogy and Psychology, 2022)
The purpose ofthe article isto show how you can work with termsin classesin theRussian language as a non-native with students of the specialty “Electric Power Engineering.” The authors proceed from the assumption that pre-text work should precede work with the text. Students should have an idea of ​ ​what terms are and which units function like them. A number of terms are considered-therminoids-nomens-expressive words expressing special concepts. Terminology, thermo system, thermo field are analyzed from the point of view of the relations in which the terms are found: paradigmatics-thermo system,syntagmatics-thermo field,simple totality - terminology. The text in the specialty is a thermopol, in which the context that semantises key concepts acquires significance. When selecting educational texts, the complexity and terminology coefficient for different levels of language proficiency is taken into account. For the educational text, such components of the complexity of the text as informativity, linguistic complexity, clarity of structure, abstract presentation are important